Prospective uses of recombinant Lactococcus lactis expressing both listeriolysin O and mutated internalin A from Listeria monocytogenes as a tool for DNA vaccination - de Azevedo, M. S. P. (2015)
In this study, Lactococcus lactis was engineered to express mutated internalin A on its surface and to secrete large amounts of listeriolysin O (LLO) in order to improve its potential as a vehicle for DNA vaccination. Western blotting experiments demonstrated that the bacterium expressed LLO in both the cytoplasmic and extracellular compartments, with higher quantities found in the culture supernatants. A hemolytic assay showed that the recombinant strain secreted 250 ng active LLO/mg total protein. This mInlA/LLO-producing strain of L. lactis may be used as an alternative tool in DNA vaccination against a number of infectious diseases or in cancer therapy.